A MODERN TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES DIGITAL GENERATION OF STUDENTS: MODERN TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES DIGITAL GENERATION OF STUDENTS - Kavilova, Tamara (Журнал иностранных языков и лингвистики, 2022)
The article is devoted to modern technologies, their didactic potential, the use of a foreign language in teaching the digital generation of students. The article notes the factors contributing to the introduction of new technologies, the psychological characteristics of the digital generation.